2011
DOI: 10.3758/s13415-011-0051-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the brief viewing of emotional stimuli on understanding of insight solutions

Abstract: In the present study, we examined whether and how brief viewing of positive and negative images influences subsequent understanding of solutions to insight problems. For each trial, participants were first presented with an insight problem and then briefly viewed a taskirrelevant positive, negative, or neutral image (660 ms), which was followed by the solution to the problem. In our behavioral study (Study 1), participants were faster to report that they understood the solutions following positive images, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 67 publications
(113 reference statements)
0
16
0
Order By: Relevance
“…This result, as well as the negative correlations between flow and visual search time, could be due to type of task or type of abilities 31) . Although previous studies reported that positive emotion facilitates flexible thinking 32) and verbal ability 33) , implicit learning in contextual cueing might occur almost independently from emotional responses, including flow. It has also been shown that positive emotion impedes a logical 34,35) and careful way of thinking 36) .…”
Section: Discussionmentioning
confidence: 90%
“…This result, as well as the negative correlations between flow and visual search time, could be due to type of task or type of abilities 31) . Although previous studies reported that positive emotion facilitates flexible thinking 32) and verbal ability 33) , implicit learning in contextual cueing might occur almost independently from emotional responses, including flow. It has also been shown that positive emotion impedes a logical 34,35) and careful way of thinking 36) .…”
Section: Discussionmentioning
confidence: 90%
“…It also matches our everyday experience of insight as a very pleasant event. Further, positive affect is known to facilitate insight (e.g., Isen et al, 1987; Bolte et al, 2003; Subramaniam et al, 2009; Sakaki and Niki, 2011). The present finding that feeling happy or in a good mood predicts a global rating of Aha!…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that arousal plays a more crucial role in subsequent association learning for harbinger cues than valence (i.e., positive or negative). However, positive and negative emotions sometimes impact cognitive processing differently (Sakaki, Gorlick, & Mather, 2011; Sakaki & Niki, 2011; Schmitz, De Rosa, & Anderson, 2009). Future work is needed to test the effects of contingency awareness for cues that predict emotionally positive outcomes.…”
Section: Discussionmentioning
confidence: 99%